Analysis of the Guiding Role of CYP2C19 Gene Combined With Platelet Function Detection in Antiplatelet Therapy in Patients With Complex Coronary Artery Disease After PCI - Yu, Jiancai; Liu, Yongxing; Peng, Wanzhong; Liu, Juan; Li, Ya; Liu, Junyan; Jiang, Yang; Liu, Demin; Xu, Zesheng (Frontiers in Surgery, 2022)
[Abstract] Objective: To explore the influence of CYP2C19 gene combined with platelet function test on clinical prognosis of patients with complex coronary artery disease receiving antiplatelet therapy after PCI. Methods: A total of 200 patients undergoing PCI in our hospital due to complex coronary artery disease from February 2019 to February 2021 were selected and divided into the control group and the observation group according to whether CYP2C19 gene detection was performed. The control group was treated with dual antiplatelet therapy of classical aspirin combined with clopidogrel, and the observation group was treated with individual antiplatelet therapy. The patients in the two groups were followed up for 1 year after PCI, and their quality of life was assessed using the Seattle Angina Questionnaire (SAQ score). The occurrence of major adverse cardiovascular events (MACE) during the follow-up period was also recorded. Results: The incidence of total MACE events in the observation group was slightly less than that in the control group, and the difference was statistically significant (P=0.040). In particular, the observation group was superior to the control group in reducing the readmission rate of recurrent unstable angina pectoris, and the difference was statistically significant (P=0.023). The location of coronary culprit lesions with recurrent ischemic events was commonly seen in non-interventional target lesions (interventional/non-interventional target sites: 12.9%: 77.1%). The SAQ score in the observation group was larger than that in the control group, and the difference was statistically significant (P=0.012). There was no statistical difference in the incidence of major bleeding between the two groups (P=0.352). Conclusion: Using CYP2C19 genotype combined with platelet function test to guide individualized antiplatelet therapy after complex coronary artery PCI is beneficial to reducing ischemic events in a short period (1 year), mainly due to reducing the risk of readmission for recurrent unstable angina pectoris, and improving the quality of daily life of patients without increasing the risk of massive hemorrhage, which can improve clinical prognosis.